Vertical siting of an overtopping open pier for Brgy. Palani, Balud, Masbate using Delft3D - Verzosa, Frances Margarette L.
Brgy. Palani in Balud, Masbate has a high potential for tourism owing to its 10 km stretch of fine white sand beach. Tourism would introduce new livelihood opportunities for Baludenos who subsist on agriculture and fishing. Unfortunately, there is no direct travel option to Palani and all routes consist of multiple, inconvenient transfers. A pier must be designed for Palani to provide accessibility and jumpstart the development of tourism. This study aims to provide the required minimum overtopping elevation of an open pier for Brgy. Palani, Balud, Masbate through vertical siting in consideration of critical storm tide levels. To simulate critical conditions, two historically critical typhoons are selected based on maximum wind speed (Vmax), radius of maximum winds (Rmax), closest distance, and track relative to the site. The storm tides are separately simulated on a calibrated and validated hydrodynamic model. The software used is Delft3D, an open source, fully integrated flow and transport modeling system for coastal, river, and estuarine areas. The parameters considered in the vertical siting of an overtopping open pier are storm tide levels. Due to limited availability of observed data for validation, only typhoons from 2008 to 2017 are analyzed. Of the 10 potentially critical typhoons, Rammasun (2014), local name Glenda, and Hagupit (2014), local name Ruby, are found to be critical. Both have a maximum wind speed of 157.42 kph. Rammasun has an Rmax of 24.55 km and tracked 145 km north of the site while Hagupit has an Rmax of 25.69 and tracked 64 km north of the site. Simulated storm surges are 0.13 MASL from Rammasun and 0.33 MASL from Hagupit. The peak storm tide levels along the arbitrary location of the pier are 1.46 MASL from Rammasun and 1.42 MASL from Hagupit. Based on this study, the required minimum overtopping elevation of an open pier for Brgy. Palani is 1.46 MASL.